The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.3109/02844311.2010.488886
|View full text |Cite
|
Sign up to set email alerts
|

Shortened rehabilitation period using a modified surgical technique for reconstruction of lost elbow extension in tetraplegia

Abstract: Our aim was to evaluate the functional outcome of reconstruction of elbow extension in tetraplegia using a new technique for improving the attachment sites of posterior deltoid-to-triceps transfer in conjunction with an active rehabilitation programme. Ten tetraplegic patients (15 arms) had modified deltoid-to-triceps transfer using a tibialis anterior tendon graft. The operation included large overlaps between the tendon attachments, and additional security by anchoring the distal stump of the tendon graft to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
0
6
2
Order By: Relevance
“…The average maximum moment we recorded in the biceps transfer arms (8.80 N-m) in the horizontal plane exceeds the combined average of deltoid transfer arms previously reported in the horizontal plane (5.3 N-m) [ 9 , 10 , 12 , 14 , 15 ]. Thus, although the arms with deltoid transfer we tested were weaker in elbow extension relative to other cross-sectional studies that measured isometric moments [ 10 , 12 , 14 ], on average, we expect the biceps transfer to enable greater elbow extension strength relative to the deltoid transfer when patients are candidates for either procedure.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…The average maximum moment we recorded in the biceps transfer arms (8.80 N-m) in the horizontal plane exceeds the combined average of deltoid transfer arms previously reported in the horizontal plane (5.3 N-m) [ 9 , 10 , 12 , 14 , 15 ]. Thus, although the arms with deltoid transfer we tested were weaker in elbow extension relative to other cross-sectional studies that measured isometric moments [ 10 , 12 , 14 ], on average, we expect the biceps transfer to enable greater elbow extension strength relative to the deltoid transfer when patients are candidates for either procedure.…”
Section: Discussioncontrasting
confidence: 57%
“…The average maximum moment we recorded in the biceps transfer arms (8.80 N-m) in the horizontal plane exceeds the combined average of deltoid transfer arms previously reported in the horizontal plane (5.3 N-m) [ 9 , 10 , 12 , 14 , 15 ]. Thus, although the arms with deltoid transfer we tested were weaker in elbow extension relative to other cross-sectional studies that measured isometric moments [ 10 , 12 , 14 ], on average, we expect the biceps transfer to enable greater elbow extension strength relative to the deltoid transfer when patients are candidates for either procedure. The average maximum elbow moment we measured in the deltoid transfer arms (2.74 ± 0.22 N-m) was similar to the average of arms tested by Memberg et al [ 15 ] (1.2 ± 2 N-m) and Kirsch et al [ 9 ] (2.7 ± 3.5 N-m), but weaker relative to arms tested by Lieber et al [ 10 ] (5.89 ± 0.24 N-m), Rabischong et al [ 12 ] (6.6 ± 3.9 N-m), and Turcsanyi and Friden [ 14 ] (10.4 ± 1.0 N-m).…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Reconstructive surgery of the upper extremities using tendon transfer and joint stabilizations or, more recently, nerve transfer, has become an accepted part of rehabilitation of patients with cervical spinal cord injury (2,3). Numerous case series have demonstrated that key functions, such as elbow extension and handgrip can be restored reliably in individuals affected by traumatic or non-traumatic tetraplegia (4)(5)(6)(7)(8)(9)(10)(11). Consequently, the mobility, spontaneity and independence of tetraplegic individuals can be markedly and persistently increased (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] The most common outcome measure used to assess elbow extension is the Medical Research Council (MRC) score, which grades muscle strength from 0 to 5. In a review of 14 studies reporting outcomes of triceps reconstruction including a total of 190 limbs, average postoperative elbow extension strength was an MRC score of 3.3.…”
mentioning
confidence: 99%